2017
DOI: 10.1590/s1984-29612016090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological and molecular evaluations and CT scan screening of coenurosis (Coenurus cerebralis) in sheep and calves

Abstract: The aims of this study were to diagnose coenurosis by means of computerized tomography (CT) scan imaging and molecular characterization of the CO1 gene using the polymerase chain reaction (PCR). Sheep and calves were necropsied, and CT scans on the cephalic region were performed on the animals. Sections of brain tissue infected with parasites were then stained with hematoxylin and eosin for microscopic examination. Material collected from brain cysts was fixed in 70% ethanol. PCR amplification was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Also, intermittent clockwise and anticlockwise circling was noticed in goats with at least one cyst in each cerebral hemisphere (Table 1). These results are nearly similar to the findings of cerebral coenurosis in sheep (EDWARDS & HERBERT, 1982;GAZIOGLU et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, intermittent clockwise and anticlockwise circling was noticed in goats with at least one cyst in each cerebral hemisphere (Table 1). These results are nearly similar to the findings of cerebral coenurosis in sheep (EDWARDS & HERBERT, 1982;GAZIOGLU et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Cerebral coenurosis is endemic in Middle Eastern countries, with many reports originating from Iran (KHEIRANDISH et al, 2012;MOGHADDAR, 2007;TAVASSOLI et al, 2011), Egypt (ABBAS & ELBESKAWY, 2016;AMER et al, 2017), Turkey (AVCIOGLU et al, 2011GAZIOGLU et al, 2017;GICIK et al, 2007), Jordan (ABO-SHEHADA et al, 2002) and Iraq (KARIM, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Coenurus cerebralis is a metacestode of T. multiceps that infects the small intestine of carnivores [ 10 , 11 ]. The important intermediate hosts for T. multiceps are small ruminants such as sheep and goats [ 12 ], where oncospheres that infiltrate the brain or spinal cord develop into mature coenurus cysts in the central nervous system [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT was used in the diagnosis of coenurosis in humans and other animals. Several scholars have reported that the cyst appears to be a hypoattenuating structure with a mass effect in the CT images [ 10 ]. The MRI images of the brain parenchyma infected with Coenurus cerebralis appear hypointense in the T1W image and hyperintense in the T2W image [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation